2021
DOI: 10.1038/s41392-021-00591-7
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory route is a potential way for SARS-CoV-2 to invade the central nervous system of rhesus monkeys

Abstract: Neurological manifestations are frequently reported in the COVID-19 patients. Neuromechanism of SARS-CoV-2 remains to be elucidated. In this study, we explored the mechanisms of SARS-CoV-2 neurotropism via our established non-human primate model of COVID-19. In rhesus monkey, SARS-CoV-2 invades the CNS primarily via the olfactory bulb. Thereafter, viruses rapidly spread to functional areas of the central nervous system, such as hippocampus, thalamus, and medulla oblongata. The infection of SARS-CoV-2 induces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 48 publications
3
103
0
Order By: Relevance
“… 35 Recently, Jiao et al showed SARS-CoV-2 could infect neuro-derived SK-N-SH, glial-derived U251, and brain microvascular endothelial cells in vitro without efficient replication. 10 In contrast, Schaefer et al found no evidence of the virus in post-mortem pulmonary endothelial cells of COVID-19 patients with diffuse alveolar damage by immunohistochemical staining. 36 And multiple studies challenge the identification of “virus-like particles” in endothelial cells under EM as coronavirus particles.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 35 Recently, Jiao et al showed SARS-CoV-2 could infect neuro-derived SK-N-SH, glial-derived U251, and brain microvascular endothelial cells in vitro without efficient replication. 10 In contrast, Schaefer et al found no evidence of the virus in post-mortem pulmonary endothelial cells of COVID-19 patients with diffuse alveolar damage by immunohistochemical staining. 36 And multiple studies challenge the identification of “virus-like particles” in endothelial cells under EM as coronavirus particles.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have indicated that the SARS-CoV-2 virus may retrograde axonal travel from the periphery into the CNS via the olfactory sensory neurons (or other nerve tracts). 7 – 10 However, there is currently no convincing evidence and it remains controversial that the olfactory nerve is not a likely route to brain infection in COVID-19. 11 In addition to potential CNS invasion via the olfactory route, it is potential that SARS-CoV-2 may enter the brain via the hematogenous route.…”
Section: Introductionmentioning
confidence: 99%
“…Both Huh-7 cells and SK-N-SH cells express ACE2, the receptor for SARS-CoV-2, and replication of SARS-CoV-2 in these cell lines has been reported ( Appelberg et al. , 2020 ; Jiao et al. , 2021 ; Kumar et al.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 pandemic is a global health emergency caused by the severe acute respiratory syndrome virus 2 (SARS-CoV-2), a virus from the genus Betacoronavirus and family Coronaviridae [ 1 , 2 ]. Human patient data suggest that SARS-CoV-2 may be able to infect several organs in addition to the lungs, including the heart, kidneys, and brain [ 3 , 4 , 5 , 6 , 7 , 8 ]. Infection of the male genital tract (MGT) has been reported for a variety of viruses, including filoviruses (Ebola and Marburg viruses), flaviviruses (Zika virus), and paramyxoviruses (mumps virus), with implications for sexual transmission, persistence, fertility, and testicular health [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%